(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
After the appearance of independence, India is extremely sharp in the upliftment of weaker areas, particularly tribal people. The fundamental assignment before the organizers, executives and politicians is the evacuation of social and economic inequalities and foundation of a populist society. Their fundamental fixation is on the quickened improvement of the tribals to empower them to get up to speed with further developed areas of the society. The program execution process is required to enhance their levels of living other than improving their goals and growing the world view. It is felt basic to not just examination the predominant occupational circumstance of these people yet additionally discover their advancement needs. Countless were formally declared criminal tribes from 1871 onwards. The British government in this way ran unique settlements for them where they were affixed, shackled, caned and flagellated while being encompassed by high dividers under the arrangements of the Criminal Tribes Act. In this Research paper we studied about the origin of Criminal Tribes Act and its effects on law and order.